Effects of omental pedicle transposition on regeneration of neurotmesis sciatic nerve in rabbit - Al-Timmemi, Hameed A.; Ibrahim, Rashid; Abu Bakar @ Zakaria, Md Zuki; Tengku Ibrahim, Tengku Azmi (Universiti Putra Malaysia Press, 2010)
The present study was aimed at providing an understanding of the role of omental pedicle transposition in peripheral nerve regeneration by utilizing an established rabbit sciatic nerve regeneration model. Twelve adult New Zealand White rabbits (2-2.3kg) were divided into two groups (n=6) and acclimatized for 3 weeks. Complete blood examination, liver and kidney function tests were carried out during this period. In Group A, an end-to-end of sciatic nerve segment anastomosis was done, while that of Group B, the nerve anastomosis wrapped with omental pedicle was performed. The nerve specimens were collected from both groups for histopathological and ultrastructural evaluation after 16 weeks post surgery. Results showed that omental pedicle transpositioned (Group B) had more newly developed nerve fibres and less scar tissue. Ultrastructural examinations showed neuronal sprouting, whereas directions of regenerative nerve fibres were intraneural, but in the end-to-end anastomosis of group B showed that some of nerve fibres had extraneural.